The Clinical Use of Vernier Acuity: Resolution of the Visual Cortex Is More Than Meets the Eye - Hu, Monica L.; Ayton, Lauren N.; Jolly, Jasleen K. (Frontiers in Neuroscience, 2021)
Vernier acuity measures the ability to detect a misalignment or positional offset between visual stimuli, for example between two vertical lines when reading a vernier scale. It is considered a form of visual hyperacuity due to its detectable thresholds being considerably smaller than the diameter of a foveal cone receptor, which limits the spatial resolution of classical visual acuity. Vernier acuity relies heavily on cortical processing and is minimally affected by optical media factors, making it a useful indicator of cortical visual function. Vernier acuity can be measured, usually in seconds of arc, by freely available automated online tools as well as via analysis of steady state visual-evoked potentials, which allows measurement in non- or pre-verbal subjects such as infants. Although not routinely measured in clinical practice, vernier acuity is known to be reduced in amblyopia, glaucoma and retinitis pigmentosa, and has been explored as a measure of retinal or neural visual function in the presence of optical media opacities. Current clinical utility includes a home-based vernier acuity tool, preferential hyperacuity perimetry, which is used for screening for choroidal neovascularisation in age-related macular degeneration. This review will discuss the measurement of vernier acuity, provide a current understanding of its neuro-ophthalmic mechanisms, and finally explore its utility through a clinical lens, along with our recommendations for best practice.